Correlation of type II adsorption isotherms of water contaminants using modified BET equations - Brião, Giani de Vargas; da Silva, Meuris Gurgel Carlos; Vieira, Melissa Gurgel Adeodato; Chu, Khim Hoong (Colloid and interface science communications, 2022)
The BET equation is commonly used to describe type II sigmoid isotherms of water contaminants. However, there are some type II isotherms that do not agree with the BET equation. In this paper, three modified BET equations (Aguerre–Suarez–Viollaz, Pantuso–Tolaba–Aguerre, and Aranovich–Donohue) are evaluated against published isotherm data of dysprosium, reactive blue 5G, and naphthenic acid. In the cases studied, the three modified BET equations are shown to outperform the original BET equation. The Aranovich–Donohue equation is a promising isotherm model, offering accurate data correlations and statistically significant parameter estimates. In particular, it is very effective in tracing the atypical curve shapes of the reactive blue 5G and naphthenic acid isotherms. Although the Aranovich–Donohue equation has not attracted much attention, it is a practical alternative to the widely used BET equation for correlating adsorption isotherms of water contaminants. [Display omitted] •The BET equation fits intricate type II isotherms poorly.•The Aranovich–Donohue equation outperforms the BET equation in correlating atypical type II isotherms.•The Aranovich–Donohue parameter estimates are statistically significant.